Soil quality and plant nutrition at coffee production systems - Martins Neto, Fabio Lúcio; Matsumoto, Sylvana Naomi; Souza, Antônio Jackson Jesus; Bonfim, Joice Andrade; César, Fábio Ricardo Coutinho Fontes; Lima, Jessé Moreira (Coffee Science - ISSN 1984-3909, 2011)
In the effort for the increase of the productivity, diverse used techniques, as the intensive managing of the soil, the synthetic fertilizer application and the chemical control of spontaneous herbs, have negative consequences that, in the long stated period, they work to mine the productivity of the agricultural land. The agricultural sustanability can be appraised as a group of agroecologicals requirements that must be satisfied in any property, independently of the adopted management, economic level, position in the landscape and other differences. Thus, it has a pressing necessity to organize methods of evaluation that define, in concrete way, the sustainability of this agricultural systems. Two farms in Piatã, Chapada Diamantina, Bahia, had been chosen for the evaluation of the sustainability of the unshade and shade systems of coffee production. In the soils, it was evaluated vegetal covering, the microbial activity, the organic matter and the main chemical parameters. In the cofee trees was evaluated SPAD value and foliar contents of macro and micronutrients. This work objectived the evaluation of the organic management to the agricultural support of systems. The organic coffee plantations had presented better parameters how much to the covering, the organic matter and the microbiological activity of the soil. However, the contents of nutrients in the soil and leaves were below of the adequate levels.